2021
DOI: 10.1039/d0tc05727d
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Co3O4nanoparticles to CoO monitored byin situTEM and predicted ferromagnetism at the Co3O4/CoO interface from first principles

Abstract: Nanoparticles of Co3O4 and CoO are of paramount importance because of their chemical properties propelling their applications in catalysis and battery materials, and because of their intriguing magnetic properties. Here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…[14][15][16] Cobalt oxides, representative TMOs, are a family of chemical compounds consisting of cobalt and oxygen atoms, which can exist in various stoichiometries. [17][18][19][20][21] Cobalt oxide catalyzes the oxygen evolution reaction, and two-dimensional (2D) cobalt hydroxide (Co(OH) 2 ), cobalt oxyhydroxide (CoOOH), and cobalt oxide are more efficient catalysts than their bulk counterparts. [23][24][25][26][27] Therefore, recent research is focused on the preparation of 2D cobalt oxide nanosheets with non-layered or layered structures using methods such as hydrothermal reaction, 28,29 electrodeposition, 30,31 atomic layer deposition, 32,33 and ionic layer epitaxy.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[14][15][16] Cobalt oxides, representative TMOs, are a family of chemical compounds consisting of cobalt and oxygen atoms, which can exist in various stoichiometries. [17][18][19][20][21] Cobalt oxide catalyzes the oxygen evolution reaction, and two-dimensional (2D) cobalt hydroxide (Co(OH) 2 ), cobalt oxyhydroxide (CoOOH), and cobalt oxide are more efficient catalysts than their bulk counterparts. [23][24][25][26][27] Therefore, recent research is focused on the preparation of 2D cobalt oxide nanosheets with non-layered or layered structures using methods such as hydrothermal reaction, 28,29 electrodeposition, 30,31 atomic layer deposition, 32,33 and ionic layer epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] Therefore, recent research is focused on the preparation of 2D cobalt oxide nanosheets with non-layered or layered structures using methods such as hydrothermal reaction, 28,29 electrodeposition, 30,31 atomic layer deposition, 32,33 and ionic layer epitaxy. 34 The commonly investigated phases of cobalt oxide are spinel Co 3 O 4 , hexagonal CoO (h-CoO), and cubic CoO (c-CoO), [17][18][19][20][21][22] all of which undergo phase transformations under certain conditions. 18,20 The synthesis and use of the stable phases of the cobalt oxides have received considerable attention in recent years, 35,36 and interesting studies have been reported on the thermodynamic behaviors of phase transitions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations